Prediction of dementia of Alzheimer type by different types of subjective cognitive decline - Jessen, Frank; Kleineidam, Luca; Wolfsgruber, Steffen; Bickel, Horst; Brettschneider, Christian; Fuchs, Angela; Kaduszkiewicz, Hanna; König, Hans-Helmut; Mallon, Tina; Mamone, Silke; Pabst, Alexander; Pentzek, Michael; et al. (Alzheimer's and dementia, 2020)
Introduction Subjective cognitive decline (SCD) is a risk condition for dementia, including dementia of Alzheimer type (DAT). Methods We report sensitivity, specificity, positive and negative predictive values (PPV, NPV) for conversion to all-cause dementia, and DAT in different SCD types (decline in memory, assocated worries, longitudinal consitency, of the AgeCoDe study (n = 2.402, 12 years follow-up). Results 82.7% of those converting to any dementia and 84.4% of those converting with DAT at follow-up, reported memory decline and fulfilled criteria of SCD at least at one time point before. SCD with worries at two consecutive time points showed a specificity of 92.2% for any dementia and also for DAT as well as a PPV of 44.3% for any dementia and of 36.9% for DAT at follow-up at the expense of low sensitivity. Discussion Different SCD subtypes were either sensitive or specific for future all-cause dementia and DAT in cognitively unimpaired individuals. Modest PPV of the most specific SCD subtypes were achieved in this low prevalence population.
Online veröffentlicht: 2. November 2020
Gesehen am 23.05.2024